(untitled) (LEARNing Landscapes, 2012)
This article is based on the personal narrative of a Canadian pioneer woman who grew up during the 1920s and 1930s. The story epitomizes a holistic approach to learning, which embodies facets of family, community, and the land. Conceptualized through narrative inquiry, the purpose of the article is to capture an innovative meaning for holistic education. I employ Deweyan philosophy as an analytical lens for her story and provide pedagogical relevance to the narrative.